Changes in Muscle and Cerebral Deoxygenation and Perfusion during Repeated Sprints in Hypoxia to Exhaustion - Willis, Sarah J.; Alvarez, Laurent; Millet, Grégoire P.; Borrani, Fabio (Frontiers in Physiology, 2017)
During supramaximal exercise, exacerbated at exhaustion and in hypoxia, the circulatory system is challenged to facilitate oxygen delivery to working tissues through cerebral autoregulation which influences fatigue development and muscle performance. The aim of the study was to evaluate the effects of different levels of normobaric hypoxia on the changes in peripheral and cerebral oxygenation and performance during repeated sprints to exhaustion. Eleven recreationally active participants (six men and five women; 26.7±4.2 yrs, 68.0±14.0 kg, 172±12 cm, 14.1±4.7% body fat) completed three randomized testing visits in conditions of simulated altitude near sea-level ( 380 m, FIO2 20.9%), 2000 m (FIO2 16.5±0.4%), and 3800 m (FIO2 13.3±0.4%). Each session began with a 12-minute warm-up followed by two 10-second sprints and the repeated cycling sprint (10-second sprint: 20-second recovery) test to exhaustion. Measurements included power output, vastus lateralis and prefrontal deoxygenation (near-infrared spectroscopy, delta (∆) corresponds to the difference between maximal and minimal values), oxygen uptake, femoral artery blood flow (Doppler ultrasound), hemodynamic variables (transthoracic impedance), blood lactate concentration, and rating of perceived exertion. Performance (total work, kJ; -27.1±25.8% at 2000 m, p<0.01 and -49.4±19.3% at 3800 m, p<0.001) and pulse oxygen saturation (-7.5±6.0%, p<0.05 and -18.4±5.3%, p<0.001, respectively) decreased with hypoxia, when compared to 400 m. Muscle ∆ hemoglobin difference ([Hbdiff]) and ∆ tissue saturation index (TSI) were lower (p<0.01) at 3800 m than at 2000 m and 400 m, and lower ∆ deoxyhemoglobin resulted at 3800 m compared with 2000 m. There were reduced changes in peripheral [∆[Hbdiff], ∆TSI, ∆ total hemoglobin ([tHb])] and greater changes in cerebral (∆[Hbdiff], ∆[tHb]) oxygenation throughout the test to exhaustion (p<0.05). Changes in cerebral deoxygenation were greater at 3800 m than at 2000 m and 400 m (p<0.01). This study confirms that performance in hypoxia is limited by continually decreasing oxygen saturation, even though exercise can be sustained despite maximal peripheral deoxygenation. There may be a cerebral autoregulation of increased perfusion accounting for the decreased arterial oxygen content and allowing for task continuation, as shown by the continued cerebral deoxygenation.